Consequences of Straw Burning on different carbon fractions and nutrient dynamics - Mishra, Ajay Kumar; Chaudhari, S. K.; Kumar, Parveen; Singh, Kailash; Rai, Poornima; Sharma, D. K. (Indian Farming, 2015)
Crop residue shows immense potential in terms of residue incorporation in conservation agriculture. Straw burning is a serious problem in northern India, which evokes environmental as well as health hazards. Our study suggests that initially SOC and MB-C decreases due to burning of straw after harvesting. Reduced percentage of SOC and MB-C in burnt straw field at upper (0-15 cm) and lower (15-30 cm) soil depth was 16.7% and 3.4% and 41.1% and 27.2%, respectively. Phosphorus and potassium showed increased trend in top soil layer due to straw burning while most important plant nutrient i.e. nitrogen decreased in soil samples taken from burnt straw field. The residues can be put to various uses, if managed properly. There is a need to create awareness among the farming communities about the importance of crop residues in sustainability and resilience of Indian agriculture in terms of residue management besides various health relatedissues. Government intervention is immediately warranted to popularize farm implements like zero-till seed drill, happy seeder, turbo seeder etc to avoid straw burning.